Combined effects of seawater acidification and high temperature on hemocyte parameters in the thick shell mussel Mytilus coruscus. (September 2016) - Wu, Fangli; Lu, Weiqun; Shang, Yueyong; Kong, Hui; Li, Lisha; Sui, Yanming; Hu, Menghong; Wang, Youji
Abstract: In this work, flow cytometry was used to examine the immune responses of hemocytes in the thick shell mussel Mytilus coruscus exposed to six combinations of pH (7.3, 7.7, and 8.1) and temperature (25 °C and 30 °C) for 14 days. Temperature showed significant effects on all immune parameters throughout the experiment. Generally, the total hemocyte count (THC), phagocytosis (Pha), esterase (Est), and lysosomal content (Lyso) significantly decreased at high temperature. By contrast, the hemocyte mortality (Hm) and reactive oxygen species (ROS) levels increased at high temperature. Moreover, pH significantly influenced all the immune parameters, but its effects are not as strong as those of temperature; only Hm, Est, and THC were negatively affected by pH throughout the experiment. After 7 days, low pH resulted in decreased Lyso and increased Hm and ROS levels. Significant interactions between temperature and pH in most measured parameters from 7 days suggested that long-term combined stress, i.e., low pH and high temperature, would cause more severe effects on mussel health than an individual stressor in the field. Graphical abstract: Highlights: Seawater acidification and high temperature induced hemocyte parameter changes in the thick shell mussel. High temperature induced greater hemocyte parameter alterations than low pH. Most hemocyte parameters were impaired severely by the combined stress of high temperature and acidification. Interactive effects of temperature and pH on all hemocyte parameters were found.